"THE BRIGHT BONE OF A DREAM": DRAMA, PERFORMATIVITY, RITUAL, AND COMMUNITY IN MICHAEL ONDAATJE'S "RUNNING IN THE FAMILY" - MATTHEWS, S. LEIGH (Biography (Honolulu), 2000)
In a reading of Michael Ondaatje's Running in the Family (1982) which stresses the communal identity of the autobiographical subject, this essay makes a connection between the function of life writing in modern society and that of ritual in primitive societies. The memoir form in particular is thus viewed as a tool used by marginalized individuals to achieve a public performance—a public rite of passage—as a means to reintegrate the self within communal origins and to provide critical reflection on limited Western concepts of subjectivity and historiography.